2016
DOI: 10.1016/j.pt.2016.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium Oocysts: Overlooked Targets of Mosquito Immunity

Abstract: Although the ability of mosquitoes to limit Plasmodium infection is well documented, many questions remain as to how malaria parasites are recognized and killed by the mosquito host. Recent evidence suggests that anti-Plasmodium immunity is multimodal, with different immune mechanisms regulating ookinete and oocyst survival. However, most experiments determine the number of mature oocysts, without considering that different immune mechanisms may target different developmental stages of the parasite. Complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 97 publications
10
59
0
Order By: Relevance
“…We also examined the temporal nature of an additional feeding, where mosquitoes infected with either P. berghei or P. falciparum received an additional blood-meal eight days post-infection (Figure 1F), a time in which developing oocysts have initiated sporogony (Smith and Barillas-Mury, 2016). At this stage of oocyst development, an additional blood meal does not influence P. berghei (Figure 1G) or P. falciparum (Figure 1H) oocyst numbers, which suggests there is a temporal component that determines P. berghei losses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also examined the temporal nature of an additional feeding, where mosquitoes infected with either P. berghei or P. falciparum received an additional blood-meal eight days post-infection (Figure 1F), a time in which developing oocysts have initiated sporogony (Smith and Barillas-Mury, 2016). At this stage of oocyst development, an additional blood meal does not influence P. berghei (Figure 1G) or P. falciparum (Figure 1H) oocyst numbers, which suggests there is a temporal component that determines P. berghei losses.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmodium oocysts develop in the space between the midgut epithelium and the midgut basal lamina (Smith and Barillas-Mury, 2016), providing protection from the cellular or humoral components of the mosquito immune system. To examine if an additional blood- or protein-meal could influence the integrity of the basal lamina, we utilized a collagen hybridizing peptide (CHP) that specifically binds unfolded collagen chains, to serve as an indicator of tissue damage (Hwang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation is that the majority of the immune response factors that have been described belong to the early innate immunity response that takes place between 2-24h post-infection, at the ookinete stage, where the most part of the parasite recognition and killing occur [44,45]. The samples analyzed in this study correspond to the oocyst stage, approximately six and seven days after an infective blood feeding, and the immune factors playing a role at this stage still remain poorly characterized [46].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown exquisite susceptibility of motile ookinete stage parasites to complement-like proteins produced by the mosquito innate immune cells (Molina-Cruz et al, 2015; Ramphul et al, 2015). Oocysts are likewise also vulnerable to mosquito defense mechanism (Smith and Barillas-Mury, 2016). …”
Section: Discussionmentioning
confidence: 99%